A STUDY ON RELATIONSHIP BETWEEN SOCIAL INTELLIGENCE AND ACADEMIC ACHIEVEMENT OF HIGHER SECONDARY STUDENTS - P, Sreeja; M, Nalinilatha (International Journal of Research -GRANTHAALAYAH, 2017)
The study aimed to identify the relationship between social intelligence and academic achievement of higher secondary students. The investigator adopted survey method to study the social intelligence between students from selected government, private and aided school. For this study a sample of 300 school students from eight various schools which are situated in Palakkad district selected by the investigator using simple random sampling technique. The findings revealed that there is no significant relationship between social intelligence and academic achievement. This study shows that students do not find healthy environment in schools for developing their social intelligence. The schools fail to provide a proper environment to develop better relationship, positive behavior, social skills positive attitudes and good mental health in students.